Pengaruh Implementasi Kebijakan Kawasan Perbatasan Indonesia-Malaysia Terhadap Efektivitas Ketahanan Wilayah di Kabupaten Nunukan Provinsi Kalimantan Utara - Dewi Kurniasih; Makmur Umar (Jurnal Ketahanan Nasional, 2022)
ABSTRACTThe purpose of this research was to measured the effect of implementation policy about the Indonesia-Malaysia border area on the effectiveness of regional resilience in Nunukan Regency, North Kalimantan. This research was used an explanatory method and used a quantitative approach. Data collection techniques of this research through a questionnaire. Before the questionnaire distributed to a number of respondents, the validity and reliability tests were carried out on the research instrument (questionnaire). The respondents of this study amounted to 125 people. While the data analysis technique used was a simple linear regression analysis technique. This study showed that the average score of respondents' overall responses to the variable implementation of border area policies was 4.31 on a scale of 1 – 5. This result was indicates that the border area management policy in Nunukan Regency had been implemented properly. Meanwhile, the overall average score of respondents' responses for the Regional Resilience effectiveness variable was 4.57 on a scale of 1 – 5. Since the average value was closer to the score of 5, it could be concluded that security of the border area in Nunukan Regency was very effective. Thus, the policy implementation of Indonesia-Malaysia border area simultaneously affected the effectiveness of regional resilience in Nunukan Regency, North Kalimantan Province by 4,153 with a significance value close to zero. This showed that the better of policy implementation, the more effective regional resilience in the Indonesia-Malaysia border area would be.